The (dis)saving behavior of the aged in Japan - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2009)
In this paper, I survey the previous literature on the saving behavior of the aged in Japan and then present some survey data on the saving behavior of the aged in Japan that became available recently. To summarize the main findings of this paper, virtually all previous studies as well as the newly available data I analyze find that the retired aged dissave and that even the working aged dissave, at least at advanced ages. Moreover, there has been a sharp increase in the dissaving of the retired aged since 2000, with the increase being due primarily to reductions in social security benefits, increases in consumption expenditures, and increases in taxes and social insurance premiums. These findings are consistent with the life-cycle model and suggest that this model is highly applicable (and becoming increasingly applicable over time) in the case of Japan.
Keywords: D12; D91; E21; 330; age structure of the population; aged; aging; consumption; dissaving; elderly; households; Japan; life-cycle model; life-cycle hypothesis; retirement; saving; saving rate; Sparen; Alte Menschen; Ältere Arbeitskräfte; Japan